2020
DOI: 10.1192/bjb.2020.121
|View full text |Cite
|
Sign up to set email alerts
|

Running a journal club in 2020: reflections and challenges

Abstract: Summary The online environment brings both challenges and opportunities. The skills learned in journal clubs remain highly relevant where the ability to critique rapidly generated information and apply evidence to patient care is vital. Creativity and flexibility are needed to ensure that learners’ needs are met and efforts are made to involve those who may not be naturally drawn to online environments. This article explores how journal clubs have been approached in the past, both in person and more recentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…A journal club refers to a type of an educational meeting where a group of individuals discuss and critique published articles and are being predominantly employed as an integral component of postgraduate training. 1,[14][15][16][17] This act of discussion and critique not only enables them to utilize findings of research in their practice but also acts as one of the modalities for the members to be aware of the recent developments in their fields of interest and research methodology. [15][16][17] As students have to prepare for participating in different sessions, the journal clubs provide them an opportunity to become self-directed and life-long learners, as well as play a crucial role in enhancing their inclination toward practicing in evidence-based medicine.<sup> [18][19][20] These journal clubs are conducted under the guidance of teachers or guides, and the students are the ones who make presentations to critique journal articles in the presence of other postgraduate students and department faculty members.…”
Section: Journal Clubsmentioning
confidence: 99%
“…A journal club refers to a type of an educational meeting where a group of individuals discuss and critique published articles and are being predominantly employed as an integral component of postgraduate training. 1,[14][15][16][17] This act of discussion and critique not only enables them to utilize findings of research in their practice but also acts as one of the modalities for the members to be aware of the recent developments in their fields of interest and research methodology. [15][16][17] As students have to prepare for participating in different sessions, the journal clubs provide them an opportunity to become self-directed and life-long learners, as well as play a crucial role in enhancing their inclination toward practicing in evidence-based medicine.<sup> [18][19][20] These journal clubs are conducted under the guidance of teachers or guides, and the students are the ones who make presentations to critique journal articles in the presence of other postgraduate students and department faculty members.…”
Section: Journal Clubsmentioning
confidence: 99%
“…The literature review found that online journal clubs can be more challenging to facilitate than face‐to‐face meetings, but well worth the time and investment 7 . While it can be difficult to engage larger audiences, the reach of the virtual journal club can be substantially higher than a local journal club event 8 .…”
Section: What Did We Consider?mentioning
confidence: 99%
“…In this way, online journal clubs create a venue that motivates medical professionals, increases networking, and minimizes social isolation, especially during the COVID-19 pandemic. It is worth noting that although the COVID-19 pandemic resulted in a rapid shift to online learning, online journal clubs have existed for a long time [ 8 ].…”
Section: Introductionmentioning
confidence: 99%